Impact of the constructivist model to manage university innovation in sport - Marcos Alexis Serrano Tamayo; Víctor Manuel Corona Miranda; Falconeri Lahera Martínez (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2020)
Innovation by projects is considered one of the main sources of impact of science and technology, however, the valuation of these is a problem, not yet fully resolved, despite the efforts made by different researchers and organizations, this reality does not escape the sports organizations. The aim of this article is to assess the impact of innovation by projects, managed by the Faculty of Physical Culture of Granma, from a constructivist model. The research required empirical methods such as the review of official documents, observation and interview, as well as the multivariate graphic method and arithmetic procedures; the latter allowed the impact of the innovations to be evaluated as favourable, relevant, sustainable and with performance in the saturation phase, five years after the financial execution of the projects used as a sample was concluded.